Proceedings of the Genetic and Evolutionary Computation Conference 2019
DOI: 10.1145/3321707.3321827
|View full text |Cite
|
Sign up to set email alerts
|

Offspring population size matters when comparing evolutionary algorithms with self-adjusting mutation rates

Abstract: We analyze the performance of the 2-rate (1 + λ) Evolutionary Algorithm (EA) with self-adjusting mutation rate control, its 3-rate counterpart, and a (1 + λ) EA variant using multiplicative update rules on the OneMax problem. We compare their efficiency for offspring population sizes ranging up to λ = 3, 200 and problem sizes up to n = 100, 000.Our empirical results show that the ranking of the algorithms is very consistent across all tested dimensions, but strongly depends on the population size. While for sm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…The original algorithm in [4] uses as lower bound lb = 1/n. In our previous work [18], however, we observed that a more generous lower bound of 1/n 2 can be advantageous. In particular, we observed the following effects on OneMax, for problem dimension n up to 10 5 and offspring population size λ up to 32 • 10 3 :…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The original algorithm in [4] uses as lower bound lb = 1/n. In our previous work [18], however, we observed that a more generous lower bound of 1/n 2 can be advantageous. In particular, we observed the following effects on OneMax, for problem dimension n up to 10 5 and offspring population size λ up to 32 • 10 3 :…”
Section: Introductionmentioning
confidence: 80%
“…We continue previous work summarized in [18], where we have studied the so-called 2-rate (1 + λ) EA r/2,2r algorithm suggested in [4]. The 2-rate (1 + λ) EA r/2,2r is an EA of (1 + λ) EA type with self-adjusting mutation rates.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The N -queens problem (NQP) [Bell and Stevens(2009)] is defined as the task to place N queens on an N × N chessboard in such a way that they cannot attack each other. 3 Figure 3 provides an illustration for the 8-queens problem.…”
Section: F23: N-queens Problemmentioning
confidence: 99%
“…Note that most algorithms are parametrized, and we use here in this work only standard parametrizations (e.g., we use 1/n as mutation rates, etc.). Analyzing the effects of different parameter values as was done, for example in [Rodionova et al(2019)Rodionova, Antonov, Buzdalova, andDoerr, Dang and], would be very interesting, but is beyond the scope of this present work.…”
Section: Algorithmsmentioning
confidence: 99%